"Excellent Library"—A Holistic Quality Model and Certificate for Libraries: Concept and Experiences from Germany. Issue 1 (2nd January 2017) - Vonhof, Cornelia; Bertele, Maria
ABSTRACT: In Germany, more than 15 libraries are operating successfully with the quality model Excellent Library. They are part of a research project at Stuttgart Media University where the quality model and certificate have been developed since 2008. The article reflects the experiences of the project: A short introduction to the German library system and quality projects in German libraries will be followed by an overview over the model and certificate. Furthermore, the challenging process of becoming an Excellent Library and related effects will be described.